The Transformation of Learning Outcomes through Technology in Education: A Review of the India National Education Policy 2020 (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The National Education Policy (NEP) 2020 in India has placed a significant emphasis on the transformative potential of technology in education. This research article explores the key ways in which technology can contribute to improved learning outcomes from the perspective of the NEP. A methodical search approach was utilized to get research articles that reported specific learning outcomes and focused on the use of instructional technology in higher education settings. Methodological rigor, findings validity, and relevance to the review topic were utilized to evaluate the quality of the included research. The findings of this study underscore the potential of technological innovation to transform education in India. By addressing a few challenges and leveraging the opportunities provided by technology, India can create a more inclusive, equitable, and effective education system that prepares students for the 21st century.